EIF2S1 in Urinary Extracellular Vesicles as a Novel Diagnostic Marker for Bladder Cancer - Eisuke Tomiyama; Kazutoshi Fujita; Kyosuke Matsuzaki; Ryohei Narumi; Makoto Matsushita; Yujiro Hayashi; Mamoru Hashimoto; Taigo Kato; Koji Hatano; Atsunari Kawashima; Takafumi Minami; Tetsuya Takao; et al. (Cancer Medicine)
ABSTRACT Background Urinary extracellular vesicles (uEVs), directly secreted from bladder cancer (BCa) cells, harbor potential for biomarker discovery. Methods We performed proteomic analysis to explore and validate uEV‐based diagnostic markers for BCa, with a focus on cytoplasmic EV proteins. Among the 1960 proteins identified by shotgun proteomics (tandem mass tag‐labeled liquid chromatography–tandem mass spectrometry [LC–MS/MS]) of uEVs from seven patients with BCa and four healthy individuals, 17 cytoplasmic EV proteins were significantly elevated in the patients' urine (fold change > 1.5; p < 0.05). These 17 proteins were subsequently validated using targeted proteomics (selected reaction monitoring/multiple reaction monitoring) using urine samples from 49 and 48 patients with and without BCa, respectively, including those with non‐BCa hematuria. Results Ten measurable EV proteins remained significantly elevated in the urine of patients with BCa, with EV‐EIF2S1 demonstrating the best diagnostic performance (area under the receiver operating characteristic [ROC] curve [AUC] [ROCAUC]: 0.83). Additionally, EV‐EIF2S1 distinguished patients with BCa from those without BCa and hematuria in a suitable manner (ROCAUC: 0.92). Functional analysis of EIF2S1 in the BCa cell lines (T24 and 5637) showed that EIF2S1 knockdown markedly inhibited cell proliferation and induced cell cycle arrest and apoptosis, suggesting its essentiality for BCa cell growth and survival. Conclusions This study identified EV‐EIF2S1 as a novel, uEV‐based BCa diagnostic marker and demonstrated its functional significance in BCa cell growth and survival.